Proses Rekrutmen Pada PT. Pupuk Kujang Cikampek - Harahap, Nursulnah; Suherman, Enjang; Romli, Asep Darojatul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Internship is a compulsory subject in the form of student internship placement activities, to provide insight into the application of knowledge in the business/work world. Students practice their abilities and knowledge in analyzing problems related to the field of study program that occur in the business/work world. The implementation of internship began on January 20, 2020 until February 20, 2020 at a subsidiary of PT. Pupuk Indonesia Holding Company, namely PT. Pupuk Kujang Cikampek. PT. Pupuk Kujang Cikampek is a company that manages products such as urea fertilizer, NPK fertilizer, nitrea fertilizer, and ammonia. The problem that arises in the company is that there is an employee acceptance that is not appropriate or not based on where the employee lives. Which is where the recruitment process procedure through the website of PT. Pupuk Indonesia Holding Company.